Impairments in cognitive empathy and alexithymia occur independently of executive functioning in college students with autism. (August 2019) - Ziermans, Tim; de Bruijn, Ymke; Dijkhuis, Renee; Staal, Wouter; Swaab, Hanna
Reduced empathy and alexithymic traits are common across the autism spectrum, but it is unknown whether this is also true for intellectually advanced adults with autism spectrum disorder. The aim of this study was to examine whether college students with autism spectrum disorder experience difficulties with empathy and alexithymia, and whether this is associated with their cognitive levels of executive functioning. In total, 53 college students with autism spectrum disorder were compared to a gender-matched group of 29 neurotypical students on cognitive and affective dimensions of empathy and alexithymia. In addition, cognitive performance on executive functioning was measured with computerized and paper-and-pencil tasks. The autism spectrum disorder group scored significantly lower on cognitive empathy and higher on cognitive alexithymia (both d = 0.65). The difference on cognitive empathy also remained significant after controlling for levels of cognitive alexithymia. There were no group differences on affective empathy and alexithymia. No significant relations between executive functioning and cognitive alexithymia or cognitive empathy were detected. Together, these findings suggest that intellectually advanced individuals with autism spectrum disorder experience serious impairments in the cognitive processing of social–emotional information. However, these impairments cannot be attributed to individual levels of cognitive executive functioning.